Recurrent Monostotic Fibrous Dysplasia in the Mandible - Nilton Alves; Reinaldo José de Oliveira; Denise Takehana; Naira Figueiredo Deana (Case Reports in Dentistry)
Fibrous dysplasia (FD) is a condition in which normal bone marrow is replaced by an abnormal proliferation of new fibrous connective tissue. Female patient, white, 20 years old, attended the dental clinic reporting a slow increase in volume in the right mandible region over the last 5 years. She was examined by imaging: the panoramic X-ray revealed a lesion with the appearance of ground glass while the cone-beam computed tomography showed an extensive lesion in the region of the right hemimandible. The histopathological examination was compatible with fibrous dysplasia. Bone gammagraphy was indicated, plus an endocrinological study to eliminate polyostotic forms, which produced a negative result. Monostotic fibrous dysplasia in the right hemimandible was diagnosed. Conservative surgery was carried out and after 1 year recurrence of the tumour was observed. We may conclude that conservative surgery might not be the best choice for treatment for monostotic fibrous dysplasia in the mandible and that other options must be considered, such as radical surgery or the use of bisphosphonates. In our study, we may also conclude that it is very important to explain to the patient the possibility of recurrence of the lesion and the need for monitoring with periodic imaging studies.